Effect of fatty Amazon fish consumption on lipid metabolism - Souza, Francisca das Chagas do Amaral; Garcia, Nadja Pinto; Sales, Rejane Souza de Aquino; Aguiar, Jaime Paiva Lopes; Duncan, Wallice Luiz Paxiuba; Carvalho, Roasany Piccolotto (Revista de Nutrição, 2014)
Objective: The present study aimed to evaluate the effect of feeding diets enriched with fatty fish from the Amazon basin on lipid metabolism. Methods: Male Wistar rats were divided into four groups: control group treated with commercial chow; Mapará group was fed diet enriched with Hypophthalmus edentatus; Matrinxã group was fed diet enriched with Brycon spp.; and, Tambaqui group was fed diet enriched with Colossoma macropomum. Rats with approximately 240g±0.60 of body weight were fed ad libitum for 30 days, and then were sacrificed for collection of whole blood and tissues. Results: The groups treated with enriched diets showed a significant reduction in body mass and lipogenesis in the epididymal and retroperitoneal adipose tissues and carcass when compared with the control group. However, lipogenesis in the liver showed an increase in Matrinxã group compared with the others groups. The levels of serum triglycerides in the treated groups with Amazonian fish were significantly lower than those of the control group. Moreover, total cholesterol concentration only decreased in the group Matrinxã. High Density Lipoprotein cholesterol levels increased significantly in the Mapará and Tambaqui compared with control group and Matrinxã group. The insulin and leptin levels increased significantly in all treatment groups. Conclusion: This study demonstrated that diets enriched with fatty fish from the Amazon basin changed the lipid metabolism by reducing serum triglycerides and increasing high density lipoprotein-cholesterol in rats fed with diets enriched with Mapará, Matrinxã, and Tambaqui.